2020
DOI: 10.1007/978-3-030-65745-1_3
|View full text |Cite
|
Sign up to set email alerts
|

EnCoD: Distinguishing Compressed and Encrypted File Fragments

Abstract: Reliable identification of encrypted file fragments is a requirement for several security applications, including ransomware detection, digital forensics, and traffic analysis. A popular approach consists of estimating high entropy as a proxy for randomness. However, many modern content types (e.g. office documents, media files, etc.) are highly compressed for storage and transmission efficiency. Compression algorithms also output high-entropy data, thus reducing the accuracy of entropy-based encryption detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…Mbol et al [45] use a test based on the Kullback-Liebler divergence to detect ransomware converting high-entropy JPEG files to encrypted content. Depending exclusively on randomness is dangerous [46,47] for reasons pointed out in Sect. 4.1.…”
Section: Ransomware Detectionmentioning
confidence: 99%
“…Mbol et al [45] use a test based on the Kullback-Liebler divergence to detect ransomware converting high-entropy JPEG files to encrypted content. Depending exclusively on randomness is dangerous [46,47] for reasons pointed out in Sect. 4.1.…”
Section: Ransomware Detectionmentioning
confidence: 99%
“…Entropy of binaries has also been reliably used as an indicator of maliciousness [37,49], although recent research has shown that this assumption may be flawed [38] regarding packers. This is similar to network forensics, wherein it can be assumed that entropy is an indicator of encryption and therefore maliciousness [22]. These works are only loosely related to our proposal, as they give the intuition that integrating measures of entropy as part of the features can potentially improve detection and classification results.…”
Section: Year Workmentioning
confidence: 86%
“…В [18] используется NIST для определения сжатых и зашифрованных документов. В [19] (и расширенной версии статьи [20]) для классификации шифрованного и популярных форматов сжатого трафика используется нейронная сеть со значениями функции плотности вероятности поинтервального распределения значений байтов в фрагментах данных в качестве признаков. По результатам экспериментов на наборе файлов этот метод показывает высокие качество и скорость работы, но для хороших результатов минимальный размер анализируемого фрагмента ограничен снизу примерно 2 КБ.…”
Section: обзор существующих методов решенияunclassified
“…Также есть исследования по применению искусственных сетей к решаемой задаче. Среди архитектур есть как сети прямого распространения ( [12], [19]), так и свёрточные ( [12]). В [12] авторам не удалось добиться высоких результатов классификации, хотя лучший из полученных (около 70%) всё-таки статистически превосходит классификацию случайным выбором).…”
Section: использование машинного обученияunclassified
See 1 more Smart Citation